Management model based on Lean, S OP and SLP to increase the service level in a MSE in the brewery sector (LACCEI, 2024)
This article is developed in a warehouse of a trading company belonging to the beer industry, which plays an essential role in the supply chain, since it favors delivery times and reduces financial losses in the warehouse, which allows offering better services and increase profits. In order to have an optimal handling of the products within the warehouse, it is necessary to have a greater efficiency in the fulfillment of orders. Therefore, in this case, the implementation of the Systematic Layout Planning and Sales and Operations Planning methodology has been chosen, accompanied by Lean and 5S tools, with the aim of optimizing the level of service and maximizing storage efficiency. The results of this model show the current situation of the company, which is 84.34% of the service level and increases by 96.65%, which is due to the implementation of the 5S, S OP, SLP and Standardized work. Keywords—Systematic Layout Planning, 5S, Sales and operations planning, service level, brewery sector